Understanding the Stealth Properties of PEGylated lipids: A Mini-Review - Kalyanram Poornima; Puri Anu; Gupta Anju (International Journal of Lipids, 2020)
PEGylation is a well-established strategy for improving the target specificity, circulation time and stability of liposomes, thereby improving their stealth properties. This brief review provides an insight on the composition of PEGylated liposomes and the characteristics that dictate the functionality of PEGylated liposomes such as surface density, molecular weight, presence of linkers and acyl groups. Physicochemical techniques used to characterize the PEG liposomes and test their stability are also discussed along with their clinical implications. This review provides the readers with a broad range of understanding of various PEGylated lipids, techniques to access their stability in liposomal formulations and state-of -the-art development of PEGylated liposomal formulations.